2013
DOI: 10.1007/s11682-013-9252-1
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses to erotic and other emotional stimuli in breast cancer survivors with and without distress about low sexual desire: a preliminary fMRI study

Abstract: Many breast cancer survivors report a loss of sexual desire and arousability, consonant with the new DSM-V category of female sexual interest/arousal disorder. The cause of decreased sexual desire and pleasure after treatment for cancer is unknown. One possibility is that cancer, or treatment for cancer, damages brain circuits that are involved in reward-seeking. To test the hypothesis that brain reward systems are involved in decreased sexual desire in breast cancer survivors, we used functional magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
1
8
0
1
Order By: Relevance
“…The current data identified both an arousal effect and a bias toward erotic relative to mutilation scenes in IPS. As with the LOC, this pleasure bias has been reported previously but not directly addressed (Sabatinelli, Bradley et al, ; Sabatinelli et al, ; Versace et al, ). In the primate, LIP neurons, homologous with human IPS, are sensitive to the reward value (e.g., juice) of fixation locations (Bendiksby & Platt, ; Ding & Hikosaka, ; Dorris & Glimcher, ; Roesch & Olson, ; Rorie et al, ) and, perhaps more relevant to the current study, monkeys will sacrifice these juice rewards in order to view scenes depicting socially relevant conspecifics (dominant males, sexually receptive females; Deaner, Khera, & Platt, ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The current data identified both an arousal effect and a bias toward erotic relative to mutilation scenes in IPS. As with the LOC, this pleasure bias has been reported previously but not directly addressed (Sabatinelli, Bradley et al, ; Sabatinelli et al, ; Versace et al, ). In the primate, LIP neurons, homologous with human IPS, are sensitive to the reward value (e.g., juice) of fixation locations (Bendiksby & Platt, ; Ding & Hikosaka, ; Dorris & Glimcher, ; Roesch & Olson, ; Rorie et al, ) and, perhaps more relevant to the current study, monkeys will sacrifice these juice rewards in order to view scenes depicting socially relevant conspecifics (dominant males, sexually receptive females; Deaner, Khera, & Platt, ).…”
Section: Discussionsupporting
confidence: 57%
“…In the current data set, the LOC showed two overlaid modulation patterns across the five scene categories: an arousal effect, in which pleasant and unpleasant scenes prompted enhanced BOLD signal relative to neutral scenes; and a pleasure bias, in which highly arousing erotic scenes evoked greater BOLD signal than highly arousing mutilation scenes. While the arousal effect is well established (Bradley et al, ; Britton, Taylor, Sudheimer, & Liberzon, ; Norris, Chen, Zhu, Small, & Cacioppo, ), there is also some evidence for the pleasure bias in LOC from fMRI studies of emotional scene perception, specifically in those that include erotic scenes (Sabatinelli, Bradley et al, ; Sabatinelli et al, ; Versace et al, ). However, other studies using similar paradigms and scenes have not identified this bias (Bradley et al, ; Sabatinelli et al, ; Sabatinelli, Lang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the prefrontal areas show hyperactivation in patients with hyposexual behavior, although opposite results have been found in breast cancer survivors. Indeed, Versace et al () administering pornographic pictures to these patients demonstrated a reduced activity in the PFC and ACC, suggesting that chronic stressors might be related to a top‐down regulation of the PFC on cortical and subcortical structures in the human sexual behavior network (Versace et al, ).…”
Section: The Human Sexual Behavior From a Network Perspectivementioning
confidence: 99%
“…For example, from a sample of 1,076 substance abusers, 45.2% had been suffering from sexual dysfunctions ( 18 ); out of 701 drug abusers, 36.4% reported erectile dysfunction ( 19 ); additionally, there is a higher prevalence of sexual dysfunction in female ketamine abusers with cystitis when compared with ketamine abusers without cystitis ( 20 ). Thus, we also presented non-addictive but salient cues in the form of sexual stimuli, which are known to induce activation in the hypothalamus, thalamus, amygdala, anterior cingulate gyrus (ACC), insula, fusiform gyrus, precentral gyrus, parietal cortex, and occipital cortex in healthy people ( 21 ), and reduce brain responses to sexual stimuli in the anterior cingulate and dorsolateral prefrontal cortex in breast cancer survivors with chemotherapy ( 22 ). Evidence shows that chronic illicit drug abusers (including ketamine abusers) commonly demonstrate sexual dysfunction and a previous study showed that cocaine users had smaller activation than the comparison subjects when shown a sex film ( 23 ).…”
Section: Introductionmentioning
confidence: 99%